Pengembangan Materi Berbasis Komunikasi Bilingual Bagi Civitas Akademika UIN Maulana Malik Ibrahim Malang - Jumriyah Jumriyah; Usfiyatur Rusuly (UIN Sunan Gunung Djati Bandung, 2021)
UIN Maulana Malik Ibrahim Malang tries to be a World-Class University, one of the efforts to realize it is by a Multilingual Program course for the academic community which is mandated by the Center Language Development. This course requires relevant material to develop character participants and to maximal the learning and teaching process. The purpose of this study is to describe the stages of developing bilingual communication-based materials. The development model used is the ADDIE model. The data analysis used is descriptive qualitative analysis technique and quantitative statistical analysis. The result is the development of bilingual communication-based materials with the ADDIE model with 5 stages, namely: (1) the analysis stage is student analysis, competency analysis, and material suitability analysis; (2) the design stage is compiling Arabic and English materials based on bilingual communication with the theme of daily life; (3) the development stage is validating and improving the product; (4) implementation stage is a limited trial; and (5) evaluation stage includes formative evaluation with the results of the assessment of Arabic material experts 85.3% (very good), English material experts 85.3% (very good), language learning design experts 78.4% (good), and the final result of the academic community's learning with an average score of 81 (very good).